Penerapan Hukum Pidana Adat dalam Kehidupan Masyarakat Baduy di Tengah Sistem Hukum Nasional Indonesia - Sigit Kamseno; Saifun Nufus; Robby Nurtresna; Mabsuti Ibnu Marhas; Yayatul Mu’awanah; Deandra Ramadhan; Nilam Cahya Listyani; Eka Yulia Nengsih; Musa Bahri; Tryola Nadia (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2026)
Customary criminal law is an integral part of the living legal system within indigenous communities in Indonesia. One of the indigenous groups that consistently maintains and applies customary criminal law is the Baduy community in Lebak Regency, Banten Province. This study aims to analyze the implementation of Baduy customary criminal law, forms of customary violations and imposed sanctions, the role of customary institutions in resolving customary criminal cases, and its relevance within the Indonesian national legal system. This research employs a qualitative method with a juridical-empirical approach, using literature review and observation techniques. The findings indicate that Baduy customary criminal law is applied based on the principles of pikukuh karuhun, emphasizing the restoration of social and cosmic balance rather than retributive punishment. The resolution of customary violations is conducted through customary deliberation, with customary leaders playing a central role. Baduy customary criminal law has proven effective in maintaining social harmony within the indigenous community and aligns with the concept of restorative justice adopted in modern criminal law. This study concludes that Baduy customary criminal law remains relevant within Indonesia’s legal pluralism and can serve as a valuable reference for developing a more contextual and justice-oriented national legal system grounded in local wisdom.